Effect of nanosized TiO2 on photofermentation by Rhodobacter sphaeroides NMBL-02. (January 2015) - Pandey, Anjana; Gupta, Kiran; Pandey, Ashutosh
Abstract: Hydrogen, being a clean energy source is considered as a promising future fuel. In the present investigation, we have studied the H2 production by photosynthetic bacterial lab isolate Rhodobacter sphaeroides NMBL-02 in presence of TiO2 nanoparticles. The mixed phase (Anatase and Rutile) distributed TiO2 nanoparticles enhanced hydrogen production by R. sphaeroides NMBL-02 in the visible light and made the batch system operative for longer duration. The average size of the annealed TiO2 nanoparticles was between 8–20 nm with spherical shapes. There was no detectable amount of hydrogen produced by TiO2 nanoparticles alone in the same medium containing malate as carbon source. Whereas, significant amounts of hydrogen and CO2 were detected with pyruvate as carbon source in the same media which confirmed that the nanoparticles utilized pyruvate as preferred electron donor and facilitated conversion of the intermediate (pyruvate) into CO2 and H2 . Rate of H2 production was enhanced by 1.54 folds and duration 1.88 folds in the presence of 60 μg/mL concentration of annealed TiO2 nanoparticles in comparison to the control. Maximum hydrogen produced was 1900 mL/L with 63.27% malate conversion in a batch process with annealed TiO2 nanoparticles during photofermentation by R. sphaeroides in modified Sistrom's media using malate (22.38 mM) and glutamate (1.7 mM) as carbon and nitrogen sources respectively. Highlights: Effect of nanosized TiO2 has been reported on photohydrogen production by R. sphaeroides -NMBL-02. Maximum hydrogen produced was 1900 mL/L with 63.27% malate conversion with annealed TiO2 nanoparticles during photofermentation. Rate of H2 production was enhanced by 1.54 folds and duration 1.88 folds in the presence of 60 μg/mL concentration of annealed TiO2 nanoparticles.